The Role of Thevatấ appear in Tipitaka - Sriprem, Dr., Nun Boonchuay; Ñanấvuddho , Asst.Prof. Dr.Phramaha Boonsri (Journal of Dhamma for Life, 2023)
This research is qualitative, its purpose is to study the existence of deities. Principles of deities and roles of deities in the Tripitaka. The tools used in this research were documents from Buddhist scriptures and interviews with informants consisting of monks, nuns, Buddhist scholars, and Buddhists, totaling 40 people. The research results found that the deities in the Tipitaka who reside in the 26 levels of heaven are the 6 levels of deities who live on divine food. Rupabrahma 16 and Arupabrahma 4 live with contemplation. The principles of the gods are shame and moral fear, good conduct, fulfillment, Vattapada, the virtue of the righteous, noble treasure, and a way of making merit. The gods must live the divine virtue. The great Deva has the duty to rule over the deities and protect human beings who practice asceticism, they helped poor human beings who aim for good deeds also. From the interviews with the informants, it was found that deities reside in heaven having morality as a principle. Those gods are symbols for humans to do good deeds and avoid all bad. As chief Deva has the duty to rule the gods and have a care or dharma conversation with the Buddha and the disciples in Buddhism.